NAUFO: An extension program experience and the insertion in the cinema made in Goiás - Rodrigues Oliveira, Thais (Guará Journal, 2019)
This article reports the experience in project Foleys Center of Audio-visual  Production  (NAUFO)  from  State University  of  Goiás  (UEG).  For  this,  it  is  firstly  an approach  to  the  importance  of  extension  in  uni-versity, we pointed the cinema and audiovisual in the state of Goiás, the  sound  of  cinema  and  what  functions  the sound  professional  performs  during  the  process  of creating  and  developing  a  movie.  Finally, to relate the function of this professional to the realization of short films produced in the State of Goiás, and the importance of the extension project in the training of professionals for the local audio-visual production.
Keywords: Sound for film; Foley; Cinema in Goiás